Book Review: Jola Gjuzi, Stabilization Clauses in International Investment Law: A Sustainable Development Approach (Springer Publishing, Switzerland, April 2018) - Akalu, Mulugeta (Bahir Dar University Journal of Law, 2022)
This book review assesses and evaluates of the book that narrates the inherent contradiction between stabilization clauses and the regulatory power of the host states and attempts to reconcile the conflict using the principle of sustainable development .1The book is of typical significance for students, academics, practitioners of law and policy makers engaged in the field of international investment arbitration. The book explores the rationale why stabilization clause emerged in international investment contracts, why multinational companies prefer them and why host states adhered to insert them. It then analyzes how stabilization clauses began to defeat the regulatory rights of the host states and how their right to regulate in the public interest particularly in the areas of environmental protection and human rights are at stake. The book then suggests the reconceptualization of sustainable clauses and application of the â€œPrinciple of constructive Sustainable Developmentâ€, whose international legal status is controversial and whose meaning is yet to be clear, as a reconciliatory concept to mitigate the effects of stabilization clause on the regulatory space of the host states and to iron out the stabilization/ regulation controversy.